How Good Corporate Governance Principles Influence Corporate Social Responsibility Disclosure? - Risalatul Maghfiroh; Indah Purnamawati; Oktaviani Ari Wardhaningrum (Accounthink : Journal of Accounting and Finance, 2024)
Abstract This study aims to analyze the influence of transparency, accountability, responsibility, independence, and fairness on Corporate Social Responsibility (CSR) disclosure. The research focuses on mining companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sample was selected using a purposive sampling method, resulting in 44 companies. The analysis method used was panel data regression with the Fixed Effect Model (FEM). The results indicate that transparency and accountability do not have a significant impact on CSR disclosure. However, responsibility and independence are found to significantly influence CSR disclosure, while fairness does not show a significant effect. These findings suggest that while companies prioritize social responsibility and independence in their governance, transparency, accountability, and fairness may not be key drivers for CSR disclosure in the mining sector. This research highlights the need for better governance practices and clearer disclosure standards, particularly in industries with significant environmental impact. Keywords: corporate social responsibility, disclosure, good corporate governance principles.